Optimization of in situ transesterification of wet microalgae chlorella vulgaris under subcritical conditions - Felix, Charles B. (Animo Repository, 2016)
Microalgae are one of the most promising feed stocks for the production of biodiesel. However, the conventional production of biodiesel from microalgae requires the biomass to have minimum water content after cultivation and harvest. The consequent costs and energy consumption in the dewatering and oil extraction phases make them less attractive compared to their fossil-based fuel counterparts. A direct or in situ transesterification technique which can generate biodiesel without the need for extraction and possibly the drying process is now being investigated as a response to those issues. In an effort to further increase the product yields, the process can be subjected under subcritical conditions to make it less sensitive to the moisture and free fatty acid content of the biomass, and to eliminate the use of certain catalysts. Three variables directly affecting the biodiesel yield under this condition were investigated in a designed experiment to maximize the product yield and minimize the power consumption of the working reactor. These factors were the reaction temperature, reaction time and solvent amount, in terms of the solvent-to-solid ratio. The regression model as well as the optimal operating conditions formulated were validated by actual experiments. The fuel properties obtained under this conditions were also predicted by empirical equations and compared with more popular feed stocks. Lastly, a simple comparison between the conventional and in situ approach was made to justify the benefits of latter.